Cancer Microenvironment and Endoplasmic Reticulum Stress Response - Claudia Giampietri; Simonetta Petrungaro; Silvia Conti; Antonio Facchiano; Antonio Filippini; Elio Ziparo (Mediators of Inflammation)
Different stressful conditions such as hypoxia, nutrient deprivation, pH changes, or reduced vascularization, potentially able to act as growth-limiting factors for tumor cells, activate the unfolded protein response (UPR). UPR is therefore involved in tumor growth and adaptation to severe environments and is generally cytoprotective in cancer. The present review describes the molecular mechanisms underlying UPR and able to promote survival and proliferation in cancer. The critical role of UPR activation in tumor growth promotion is discussed in detail for a few paradigmatic tumors such as prostate cancer and melanoma.